Analysis of heat transfer in grooved plain carbon steel tube for solar applications. (2020) - Naveenkumar, R.; Karthikeyan, N.; Gopan, S. Nandha; Rajaram, S.; Ravichandran, M.
Abstract: A computational fluid dynamics study is conducted in pressure drop and thermal performance of a plain material tube and plain material tube enriched with square, circular and trapezoidal internal grooves. The computational fluid dynamics (CFD) is an authoritative method to evaluate the thermal properties for high Reynolds number condition in water heating using solar energy. A transition in flow from laminar to turbulent condition there prevails an enhancement in Nusselt number (Nu), thermal performance and pressure drop. However, for turbulent flow condition an increase in flow rate and Reynolds number (Re) the value of friction factor decreases for plain material tube and internal grooved tubes. The computational fluid dynamics results indicates that trapezoidal shaped grooving tubes attains the maximum value of drop in pressure, thermal performance and Nusselt number as compared to plain material tube and other grooved tubes pertaining to turbulent flow condition of Re from 5500 to 11500. The output signifies that the highest enhanced value of reduction in pressure attained in trapezoidal, circular and square grooving tubes are 68%, 65% and 63%. The CFD results also indicate that the highest value of increase of heat transfer rate (Q) is attained in trapezoidal grooved tube as 27%. The enhancement in Q value pertaining to circular and square grooved tubes are 21% and 14%.